Elevated levels of active Transforming Growth Factor β1 in the subchondral bone relate spatially to cartilage loss and impaired bone quality in human knee osteoarthritis. Issue 6 (June 2022) - Muratovic, D.; Findlay, D.M.; Quarrington, R.D.; Cao, X.; Solomon, L.B.; Atkins, G.J.; Kuliwaba, J.S.
Summary: Objective: The association between the spatially distributed level of active TGFβ1 in human subchondral bone, and the characteristic structural and cellular parameters of human knee OA, was assessed. Design: Paired subchondral bone samples from 35 OA arthroplasty patients, (15 men and 20 women, aged 69 ± 9 years) were obtained from beneath macroscopically present (CA+) or denuded cartilage (CA-) to determine the concentration of active TGFβ1 (ELISA) and its relationship to bone quality (synchrotron micro-CT), cellularity, and vascularization (histology). Results: Bone samples beneath (CA-) regions had significantly increased concentrations of active TGFβ1 protein (mean difference: 26.4; 95% CI: [3.2, 49.7]), when compared to bone in CA + regions. Trabecular Bone below (CA-) regions had increased bone volume (median difference: 4.3; 96.49% CI: [-1.7, 17.8]), increased trabecular number (1.5 [0.006, 2.6], decreased trabecular separation (−0.05 [-0.1, -0.005]), and increased bone mineral density (394.5 [65.7, 723.3]) comparing to (CA+) regions. Further, (CA-) bone regions showed increased osteocyte density (0.012 [0.006, 0.018]), with larger osteocyte lacunae (39.8 [7.8, 71.7]) that were less spherical (−0.02 [-0.04, −0.003]), and increased bone matrix vascularity (12.4 [0.3, 24.5]) compared to (CA+). In addition, increased levels of active TGFβ1 related to increased bone volume (0.04 [-0.11, 0.9]), while increased OARSI grade associated with lacunar volume (−44.1 [-71.1, −17.2]), and orientation (2.7 [0.8, 4.6]). Conclusion: Increased concentration of active TGFβ1 in the subchondral bone of human knee OA associates spatially with impaired bone quality and disease severity, suggesting that TGFβ1 is a potential therapeutic target to prevent or reduce human OA disease progression.